НӨКИС ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА - Есназарова, З.Б. (FAN va JAMIYAT, 2017)
The article is dedicated to the 26th anniversary of the Independence of the Republic of Uzbekistan, to the issues of housing construction in the city of Nukus for 26 years. The first President of the Republic of Uzbekistan I.A.Karimov, paid special attention to the fields of architecture and constructions. Normative documents of large capital construction before 1990 did not meet modern requirements. In this connection, decrees and resolutions were adopted. According to them in 2011-2016, certain housing and construction works were carried out. The article gives information on the organizational work of such enterprises as Binocor", "Amudaryo", "Davrurlisi"that are carrying out the housing and construction works of Ispak, such as " There author also gives the data on the strategy of actions for 2017-2021.